A Case of Donor‐Transmitted Non‐Small Cell Lung Cancer After Liver Transplantation: An Unwelcome Guest. (12th February 2019) - Sonbol, Mohamad B.; Halling, Kevin C.; Douglas, David D.; Ross, Helen J.
Abstract: Cancer transmission with organ donation has been previously reported with a variety of malignancies and organ transplants. The risk of transmission through organ transplantation from donors with a history of previously treated malignancies has been addressed by guidelines from transplant societies. Herein, we report a case of a patient who developed lung cancer confined to the liver after liver transplantation with no known history of malignancy in the donor. The suspicion of donor origin arose after positron emission tomography‐computerized tomography scan showed metastatic lung cancer only involving the transplanted liver without a primary focus. Genetic analysis of the malignant cells confirmed donor origin of the cancer. Abstract : Although it poses a risk of cancer transmission to the recipient, transplantation from a donor with history of malignancy is not always a contraindication for organ donation. This brief communication reports a case of donor‐derived malignancy that occurred after liver transplantation.